Climate of the Romanian Carpathians: Variability and Trends - Micu, D.M (Springer, 2015)
This book is a comprehensive climatic monograph, which addresses one of the most complex mountain environments in Europe, the Carpathians Chain, focusing on the branches that lie over Romania. The volume aggregates high quality input data, state-of-the-art techniques, regional analysis and overview perspectives, while addressing the spatial and temporal patterns of the main climatic elements. The study covers the period 1961-2010, for the present climate, while the perspective is extended up to 2050. The main climatic elements (e.g. air temperature, precipitation, wind) are analyzed, but some specific variables like snow depth and snow cover are also examined, both in terms of average behaviour and extreme characteristics. This is the first synthesis addressing the climate of this mountain region, and it provides useful information for scientists, mountain stakeholders, decision-makers and general public.